Caracterização da enzima citidina monofosfato quinase (EC 2.7.4.14) de Mycobacterium tuberculosis H37Rv como alvo para o desenvolvimento de drogas para o tratamento da tuberculose - Jaskulski, Léia (2013)
Tuberculosis (TB), one of the oldest recorded human afflictions, is still one of the biggest killers among the infectious diseases. The HIV co-infection and the emergence of multidrug resistant TB have provided a very alarming challenge to global health and led us to focus on the research for new and more effective therapeutics against the disease. The modern approach to the development of new chemical compounds against complex diseases, especially the neglected endemic ones, such as TB, is based on the use of defined molecular targets. Enzymes from the pyrimidine biosynthesis pathway have been considered potential targets for identification or development of novel anti-mycobacterial agents since in bacteria, pyrimidine nucleotide interconvertion pathways are important in a number of essential processes, including DNA, RNA, and phospholipid biosynthesis. Cytidine 5 -monophosphate kinase from Mycobacterium tuberculosis (MtCMK) catalyzes the ATP-dependent phosphoryl group transfer preferentially to CMP and dCMP. Here, initial velocity studies and Isothermal Titration Calorimetry (ITC) measurements showed that MtCMK follows a random-order kinetic mechanism of substrate binding, and an ordered mechanism for product release. The thermodynamic signatures of CMP and CDP binding to MtCMK showed favorable enthalpy and unfavorable entropy, and ATP binding was characterized by favorable changes in enthalpy and entropy. The contribution of linked protonation events to the energetics of MtCMK:phosphoryl group acceptor binary complex formation suggested a net gain of protons. Values for the pKa of a likely chemical group involved in proton exchange and for the intrinsic binding enthalpy were calculated. The Asp187 side chain of MtCMK is suggested as the likely candidate for the protonation event. Data on thermodynamics of binary complex formation were collected to evaluate the contribution of 2 -OH group to intermolecular interactions. The data are discussed in light of functional and structural comparisons among CMP/dCMP kinases and UMP/CMP ones.